Estratégias de enfermería para la administración de antibióticos parenterales en los servicios de cirugía, traumatología y medicina interna del Hospital José María Velasco Ibarra de Tena. - Martínez Arias, Aura Cristina (2016)
This research project was conducted at the José María Velasco Ibarra Hospital in Tena. Its objective was to develop nursing strategies for the administration of parenteral antibiotics in the hospital's surgery, trauma, and internal medicine departments.A descriptive and correlational field study was conducted. The unit of analysis was the activities related to the administration of parenteral antibiotics, which nursing staff performed in these services using survey techniques and observation guides to diagnose the current situation and its relationship with the variables under study.The results obtained allowed us to identify that some nursing staff working in the departments investigated have certain pharmacological deficiencies, the most significant of which were related to reconstitution, dilution, and speed of administration, with error rates of 48%, 72%, and 92% respectively. This, in turn, allows us to assess the existence of certain risk factors for patient safety that could lead to adverse events related to antibiotic therapy.Faced with this situation, it was decided to develop nursing strategies based on the results obtained. These strategies were validated by a multidisciplinary team of professionals with expertise in the subject. They believed they would contribute to improving the administration of these drugs in the departments studied, strengthening this important activity within the field of nursing.